(untitled) (Research, Society and Development, 2023)
Psychological Prenatal (PNP) is a complementary strategy to the traditional prenatal model that seeks to promote comprehensive care and minimize the risks of postpartum depression (PPD). This article aims to analyze data from Brazilian scientific production that deal with the PNP model. The study was carried out through a bibliographic survey using the integrative literature review method. Searches for scientific productions were carried out in January 2023, in the database of the Virtual Health Library (BVSalud), in the CAPES Periodicals and in Google Scholar, using the term “Psychological prenatal” as a descriptor. We found 32 articles that, after the selection criteria, resulted in the analysis of 07 studies. From the analysis of the articles, we observed aspects related to the PNP acting in the prevention of PPD; their contributions to the mental health of pregnant women; the risk and protective factors for PPD and the structure of the program. Thus, this integrative review highlights the preventive potential and the important health promotion tool that the PNP model proposes, as well as the centrality of the psychology professional for the success of the intervention.